Fronteiras, vivências e memórias: Moisés Santiago Bertoni e as centralidades - Portz, Solange da Silva (2020)
This research is about Moisés Santiago Bertoni, born in Switzerland in 1857, a migrant in the Triple Frontier of Argentina, Paraguay and Brazil, who died in 1929 in Brazilian land, being buried in Paraguayan land. The objective was to study recorded experiences and memories that were built and under construction on a frontier that was involved in disputes over centrality in the late 19th and early 20th centuries. Dialogues, analyzes and reflections were made to know the frontier by the records from a single person, seeking the general perspective on the particular, the details, the micro. The investigative work was being designed and structured based on what the sources were presenting, based on the contributions of Ginzburg (1989, 2004, 2007, 2009) and Beunza (2004, 2019), and the revealed evidence contributed to continue the following steps, allowing to compose parts of the investigation. The privileged sources were letters, images, maps and texts produced and kept by Bertoni and his family. Also, texts about him, such as biographies and articles found in written newspapers, produced after his death. The texts and data on Bertoni present versions that show romanticized and idealized images, sometimes contradictory. They allow an understanding about the process of building memories about this migrant of the Triple Frontier. It was found that there are interpretations built over time that seek to determine and define this character as wise, fearless and persistent. Bringing a positive image, an idealizing and contradictory discourse of a convinced anarchist, of a man who was dedicated to science and the consolidation of the image of an immigrant who adopted Paraguay as his homeland and who dedicated his life to contribute to studies and in the search for an identity of the Guarani land. It was possible to get into the complexity of what was and still is his image, a frontier haracter who knew how to experience the frontier in its multiple aspects, through study and research, whether on the natural or social environment, and through production and its Comercial relations. The frontier was visualized as a triangular space in constant movement of people, goods, ideas and knowledge. The evidence gradually revealed peculiarities about his trajectory and the world around him. When assembling this mosaic of memories based on documental diversity, the traces that led to glimpse the centrality of the frontier were being drawn on the map. The Paraná River was conceived as a central setting for Bertoni's memories and experiences, it also contributed to reflections on the various faces of the border.